If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = 14 + 6X Reorder the terms: 2 + 5x = 14 + 6X Solving 2 + 5x = 14 + 6X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 14 + -2 + 6X Combine like terms: 2 + -2 = 0 0 + 5x = 14 + -2 + 6X 5x = 14 + -2 + 6X Combine like terms: 14 + -2 = 12 5x = 12 + 6X Divide each side by '5'. x = 2.4 + 1.2X Simplifying x = 2.4 + 1.2X
| 13(17-x)=15(x+1) | | -7(1-2x)+8=-83 | | g(x)=3(5)x | | 4r^2-r+3=0 | | 3v+6=9-3(2v-2) | | x+3(x+6)=4(2x+1) | | 4(3z-3)=18 | | (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 | | 4x+4+8+2x=3(x+5) | | 3u^2+17u+24=0 | | 4x+6(x+2)=35 | | (5x-3)/9=-2 | | 2/3x5/6x14x18 | | -8(3x+1)-4=11 | | 3000(x+100)=2000(x-100) | | -4-8y=35 | | 2(x-5)(x+4)=0 | | 2x-5+8x=7-4x-12 | | 2(14+2x)=8(2+x) | | 2•1/3•3.14•25•25•25 | | 2u^2+15u+28=0 | | 4x+9x-34=68-4x | | -14=-3x | | 3x+7=5x+1-x | | 10/12*1/4= | | y=log^4(3x+11)-5 | | 6.1-0.25(x-8)=0.7x+0.3(x-3) | | 8y+9=6y+14 |